The Processing of Industrial Tofu Dreg Waste into Animal Feed in Sumurrejo Village, Semarang - Kusumaningtyas, Ratna Dewi; Hartanto, Dhoni; Prasetiawan, Haniif; Triwibowo, Bayu; Maksiola, Masni; Kusuma, Andre Dianata Hogi; Fidyawati, F; Mezaki, Naufal Mudrik; Mutaqin, Afrizal Mai; Loveyanto, Rendy Okta (Rekayasa : Jurnal Penerapan Teknologi dan Pembelajaran, 2020)
Tofu is famous as a favorite, healthy, nutritious and cheap food in Indonesia. The tofu industry has been growing rapidly in this country in the form of household scale businesses or MSME (Micro, Small and Medium Enterprises). Among the tofu MSME centers in Semarang is the one in Sumurrejo Village, Gunungpati District. Sumurrejo village has various business potentials that are capable of driving the community’s economy, especially the entrepreneurship of tofu and tempeh MSMEs, as well as dairy and beef cattle farming. The MSMEs in this area are growing rapidly and able to improve the economy of the local community. In spite of this positive impact, the existence of tofu industry also has a negative effect since its waste causes environmental pollution problems. One of them is tofu dreg waste which can cause pollution to the environment due to its bad smell, organic matters content, and putrefaction potential. One effort to overcome this problem is to process the tofu dreg waste into animal feed. Tofu waste has high nutritions which consist of 8.66% protein, 3.79% fat, 51.63% water and 1.21% ash. Therefore, in order to resolve the environmental problems caused by the disposal of tofu waste and the problem of the high price of commercial animal feed, it is necessary to conduct community service activities to increase the added value of tofu waste by processing it into animal feed through fermentation process. Tofu pulp fodder produced in this activity was also tested on chickens. Chickens that were feed with tofu waste shown a better weight gain than those given regular fodder (pur). Training on tofu waste processing into fodder was very useful for the community within the area of the tofu industry in Sumurrejo Village because it could overcome the environmental problems caused by tofu dreg waste and could provide cheap, nutritious, safe animal feed and support the livestock growth. Community service activities were conducted by providing knowledge and skills through lecturing, practice and skills training, as well as monitoring activities.